Ruch wędrówkowy ludności w aglomeracji wrocławskiej w latach 1999-2003 - Mika, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents the changes in the migration movement in the Wroclaw agglomeration and, in particular, the migration movement of population in the municipalities bordering directly on the Wroclaw city. The data used in this work came from the Bank of Regional Data presented on the website of the Central Statistical Office. The inflow and outflow coefficients and the balances of the internal migrations were the parameters used in the analysis of the studied phenomena. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1143, s. 139-148